Interferon-β gene transfer inhibits melanoma cells adhesion and migration - Rossi, Úrsula A. (2017)
We evaluated the effects of expression of interferon-β (IFNβ) after lipofection on melanoma cells adhesion and migration. Three canine mucosal (Ak, Br and Ol) and one human dermal (SB2) melanomas were assayed. By means of the wound healing assay, we found a significant inhibitory effect of canine IFNβ gene expression on cells migration in Br and Ol monolayers. This effect could be reproduced on unlipofected Ol cells with conditioned culture media obtained from canine IFNβ gene-lipofected Ol cells, and with recombinant human IFNβ on unlipofected SB2 cells. Furthermore, IFNβ gene expression of the four tested tumor cells significantly inhibited their adhesion to extracellular matrix (ECM) proteins and their spreading from multicellular spheroids onto gelatin coating. The addition of catalase reverted the increase of reactive oxygen species (ROS) in Ol cells and the inhibition of cell migration in monolayers (Ol) and spheroids (Ol an SB2) produced by canine and human IFNβ expression, suggesting the involvement of ROS as mediators of IFNβ action on the cells interactions with ECM. Together with its known immune, antiangiogenic and cytotoxic effects, the present data strongly support more studies exploring the clinical potential of IFNβ for cancer therapy.